HETEROGENEITY OF EARLY RHEUMATOID ARTHRITIS PATIENTS ACCORDING TO BLOOD GENE EXPRESSION: THEORETICAL BASES OF A DIFFERENTIAL THERAPY APPROACH - E V Chetina; N V Demidova; D E Karateev; E L Nasovov (Научно-практическая ревматология)
Objective: to assess disease severity in relation to the expression of cell-division cycle genes: p21, a cyclin-dependent kinase inhibitor; caspase 3, an apoptotic activity indicator; mammalian target of rapamycin (mTOR), a major regulator of cell growth and proliferation; ATG1, a marker of autophagy; and the proinflammatory cytokine tumor necrosis factor-α (TNF-α) in the blood of rheumatoid arthritis (RA) patients. Subjects and methods. Thirty-nine early RA patients (mean age 47.1 years) and 47 healthy individuals (mean age 43.1 years) were examined. Gene expression in their peripheral blood cells was assessed using real-time polymerase chain reaction. RA activity was estimated according to DAS28 index and joint destruction. Results. In accordance with mTOR gene expression, the group of RA patients were divided into three subgroups: 1) 18 patients had a significantly lower mTOR gene expression than did the healthy controls (p < 0.01) and upregulated ATG1; 2) 12 patients had the same mTOR gene expression levels as in the healthy controls; p21 ATG1, and caspase 3 were, however, much upregulated; 3) 9 patients showed significant upregulation of all the examined genes as compared to the healthy controls (p < 0.01). The patients from 3 subgroups differed in TNF-α gene expression that was statistically significantly exceeded that in the healthy individuals, the expression being highest in subgroup 3 patients. The subgroups of RA patients showed some differences in clinical and immunological parameters. Particularly, subgroup 2 patients exhibited the lowest morning stiffness values while subgroup 1 patients had much fewer swollen joints than did subgroup 3 patients. In addition, subgroup 2 patients had significantly statistically higher levels of anti-citrullinated antibodies whereas subgroup 3 patients had lower rheumatoid factor concentrations than the other subgroups. Conclusion. Early RA patients represent a heterogeneous group. RA patient subgroups differ in the expression of cell-cycle and TNF-α genes and in some clinical and immunological parameters. Variability in the expression of the cell-division cycle genes in different subgroups of RA patients can indicate different mechanisms involved in the development and progression of the disease and hence the necessity of applying diverse approaches to their therapy.